2021
DOI: 10.1111/jfpp.15440
|View full text |Cite
|
Sign up to set email alerts
|

The chemical, microbiological and sensory characteristics of şalgam during fermentation process

Abstract: Fermentation of dairy products, vegetables, meat, and fish is one of the oldest known food preservation method (Liong, 2015). Some fermented products (cheeses, pickles, sauerkraut, beer, and wine) are known worldwide, where most of them (brovada, boza, tarhana, kimchi) were produced as regional level by traditional methods (Erten et al., 2017). Şalgam is a local product that widely produced around Çukurova region in Turkey, and it has been an international export product over last years (Boyaci-Gunduz et al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
1
1
0
Order By: Relevance
“…According to Shalgam Beverages Standard [30], the amount of ash should be below 15 g/L in terms of dry matter [2]. The amount of ash determined in the study is compatible with the values reported by Tanguler [1], while it is lower than the values reported by Anonymous [2], Deryaoğlu [21], Cırak et al [23] and Utuş [27].…”
Section: Results Of Chemical Analysessupporting
confidence: 84%
See 1 more Smart Citation
“…According to Shalgam Beverages Standard [30], the amount of ash should be below 15 g/L in terms of dry matter [2]. The amount of ash determined in the study is compatible with the values reported by Tanguler [1], while it is lower than the values reported by Anonymous [2], Deryaoğlu [21], Cırak et al [23] and Utuş [27].…”
Section: Results Of Chemical Analysessupporting
confidence: 84%
“…According to the results obtained despite a decrease in pH, generally, this change was not found statistically significant (p≥0.05). According to Anonymous [2] and many research, it was found that the pH value of shalgam beverages without storage is between 3.30 and 3.80 [5,14,[21][22][23][24][25][26][27][28][29] so research result for initial pH value was parallel with these studies. With the fast process, it was determined as 3.58 for samples produced at 25°C and 3.50 for samples produced at 35°C.…”
Section: Results Of Chemical Analysesmentioning
confidence: 79%